Trends and prospects for developing of new industrial biotechnologies on the base of Antarctic extremophilic microorganisns - Tashyrev, O.; Romanovskaya, V.; Beregova, T.; Matvieieva, N.; Rokitko, P.; Tashyreva, G.; Falalyeyeva, T. (Ukrainian Antarctic Journal, 2010)
The aim of this study is researching Antarctic extremophilic microorganisms, estimation of trends and prospects for developing new environment protection biotechnologies, using them as producers of biologically active substances and medications. Complex structure and function researches have shown that microbial communities of Antarctic Region possess a high adaptation degree which is possible to consider as a homeostasis, i.e. preservation of viability and ability to grow in a wide range of concentration of extreme factors, down to bactericidal. The collection of the Antarctic microorganisms, resistant to extreme factors is developed. The collection includes cryoprotector-producing bacteria, microorganisms resistant to high UV radiation level (up to 500-1500 J/m2 ), isolates resistant to a wide spectrum of the most toxic metals (Hg2+, Cu2+, Cr(VI), Co2+ , Cd2+ , Ni2+ ) in concentrations of 5х102 -6х104 mg/l, isolates that are producers of biologically active substances (melanins, carotins, antibiotics etc). Isolated extremophilic microorganisms are perspective for a wide spectrum of new biotechnologies designing. Biotechnologies based on microbial mobilisation of insoluble metal compounds are effective for increase of their extraction in the mining industry, and in bioremediation. Immobilization abilities can be applied in metal-containing sewage treatment. Antarctic microorganisms can be used for new antibiotics production, antibiotic-resistant strains as test-cultures for studying efficiency of new antimicrobial preparations. Methylotrophic bacteria are perspective cryoprotector producers, pigmented microorganisms - as biologically-active substances producers (melanins, carotins). The unique yeast isolate Exophiala nigra (a melanin producer) can simultaneously be used for sewage treatment (for example, Ni2+ and Co2+ ), UV-protective preparations, creation of medicines with preventive and curative properties in relation to ulcer-erosive lesions of the stomach and precancerous states of its.